2019
DOI: 10.3390/microorganisms7120682
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Effects on Methanogenesis and Sulfidogenesis during Anaerobic Digestion of Sulfur-Rich Macroalgal Biomass in Sequencing Batch Reactors

Abstract: Methanogenesis and sulfidogenesis, the major microbial reduction reactions occurring in the anaerobic digestion (AD) process, compete for common substrates. Therefore, the balance between methanogenic and sulfidogenic activities is important for efficient biogas production. In this study, changes in methanogenic and sulfidogenic performances in response to changes in organic loading rate (OLR) were examined in two digesters treating sulfur-rich macroalgal waste under mesophilic and thermophilic conditions, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…At a global aspect, the SRP as well as Archaea abundances were affected by high temperature (See Figures 3 and 5). Our results were consistent with another study showing that both methanogenesis and sulfidogenesis were largely suppressed under thermophilic relative to mesophilic conditions [80]. SRB were more abundant at the surface of each digester compared to the bottom (Figure 4b) and were most abundant in PS (1.92 × 10 7 dsrB gene copies).…”
Section: Discussionsupporting
confidence: 93%
“…At a global aspect, the SRP as well as Archaea abundances were affected by high temperature (See Figures 3 and 5). Our results were consistent with another study showing that both methanogenesis and sulfidogenesis were largely suppressed under thermophilic relative to mesophilic conditions [80]. SRB were more abundant at the surface of each digester compared to the bottom (Figure 4b) and were most abundant in PS (1.92 × 10 7 dsrB gene copies).…”
Section: Discussionsupporting
confidence: 93%
“…In addition to that, it might also suggest that different microbial colonies might have different affinity towards the substrate. Apparently, the mesophilic colonies in 35 °C digester had more affinity towards the substrate compared to the thermophilic colonies found in higher temperature digesters (Jung et al 2019)'. The slow degradation of soluble organic matter represented as sCOD at high temperature was further supported by the accumulation of VFAs found in higher temperature digesters.…”
Section: Methane Gas Production Specific Methane Yield and Methane Compositionmentioning
confidence: 82%
“…The highest H 2 S concentration was measured as 4499 ppm on February 10, which represents the middle of winter. Jung et al [37] also observed high H 2 S concentration at low ambient temperature. It was interesting to see that the H 2 S concentration obtained in this experiment was much higher than in the laboratory experiments conducted by Saha et al [38], who obtained a H 2 S concentration of 225 ppm.…”
Section: Seasonal Variation Of Gas Compositionmentioning
confidence: 89%